2015
DOI: 10.1007/s10072-015-2161-x
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular migraine pathophysiology: insights from structural and functional neuroimaging

Abstract: Vestibular migraine (VM) has been increasingly recognized as a frequent cause of episodic vertigo, affecting up to 1 % of the general population, with female preponderance. Recently, both the Bárány Society and the Migraine Classification Subcommittee of the International Headache Society have proposed original diagnostic criteria for VM, which have been included in the recent edition of the ICHD-3 beta version. VM diagnosis implies that vestibular symptoms are present during a migraine attack, with or without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 24 publications
1
12
0
1
Order By: Relevance
“…Voxel-based morphometry studies found reductions in gray matter volumes in the inferior temporal gyrus, cingulate cortex, and posterior insula in patients with VM; these areas are involved in the cortical processing of vestibular and nociceptive information [77]. These functional and structural alterations in patients with VM resemble those previously described in patients with migraine; therefore, it is possible that VM represents a pathophysiological connection between migraine and the vestibular system [78]. …”
Section: Pathogenesis Of Vmmentioning
confidence: 83%
“…Voxel-based morphometry studies found reductions in gray matter volumes in the inferior temporal gyrus, cingulate cortex, and posterior insula in patients with VM; these areas are involved in the cortical processing of vestibular and nociceptive information [77]. These functional and structural alterations in patients with VM resemble those previously described in patients with migraine; therefore, it is possible that VM represents a pathophysiological connection between migraine and the vestibular system [78]. …”
Section: Pathogenesis Of Vmmentioning
confidence: 83%
“…While performing research on either disorder, we must keep in mind that previous work was performed when VM was not fully recognized and that it was (and is) often difficult to distinguish between VM and MD such that patients may have been mislabeled and conclusions were drawn based on historical diagnostic criteria. It may be that we will not be able to make significant strides in understanding either disease until new technology allows for novel pathways of experimentation, but we have taken important steps in recent years such as the use of new MRI protocols to image migraine and ELH in MD [ 78 80 ]. We do not wish to dishearten physicians who treat patients with dizziness by suggesting that VM and MD are far too difficult currently to distinguish and properly diagnose.…”
Section: Reviewmentioning
confidence: 99%
“…They hypothesized that subclinical vestibular dysfunction is a part of all migraine, not just vestibular migraine. Tedeschi et al reported on structural and functional neuroimaging work, highlighting evidence for abnormalities in multisensory vestibular control areas and in central vestibular processing . Russo et al presented evidence of abnormal thalamic function in response to vestibular stimulation in subjects with vestibular migraine .…”
Section: Discussion/observationsmentioning
confidence: 99%